Influence of fabric type variations on hand-written Batik quality using the Astoetik electric Batik stove - Dinda Hidayati; Kapti Asiatun; Sugiyem Sugiyem; Noor Fitrihana; Nova Suparmanto (Jurnal Pendidikan Vokasi, 2025)
This study aims to examine (1) the quality of hand-written batik produced on different fabric types using the Astoetik electric batik stove, and (2) the influence of fabric variation on batik quality outcomes. A pre-experimental one-shot case study design was employed by referring to the visual inspection procedures of hand-written batik characteristics based on SNI 8302:2016. Data were collected through structured observations and interviews, and analyzed using descriptive statistics supported by expert judgment. The findings reveal that fabric type significantly affects batik quality, particularly the width, clarity, and consistency of batik lines. The cacah gori motif produced varying line widths across fabrics: (a) 1.2796 mm on prima fabric (good quality), (b) 1.2022 mm on primissima fabric (very good effect), (c) 0.9208 mm on rayon (good quality), (d) 0.6783 mm on silk (clear inner lines, finer strokes), and (e) 1.0303 mm on santung (good batik results). Statistical testing indicated that differences across fabric types were significant. These findings were strengthened by assessments from batik experts. Overall, the variation in fabric type produced “significantly different” batik characteristics. The study suggests that fabric variation can serve as an effective learning resource in vocational batik education and can be utilized as alternative material options in the batik industry due to their potential to produce high-quality batik products.